2008
DOI: 10.1007/s00422-008-0213-5
|View full text |Cite
|
Sign up to set email alerts
|

Electric imaging through active electrolocation: implication for the analysis of complex scenes

Abstract: The electric sense of mormyrids is often regarded as an adaptation to conditions unfavourable for vision and in these fish it has become the dominant sense for active orientation and communication tasks. With this sense, fish can detect and distinguish the electrical properties of the close environment, measure distance, perceive the 3-D shape of objects and discriminate objects according to distance or size and shape, irrespective of conductivity, thus showing a degree of abstraction regarding the interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 62 publications
(86 reference statements)
1
35
0
1
Order By: Relevance
“…Although electric images can be ambiguous (Engelmann et al, 2008), conditioning experiments in Gnathonemus have shown that these ambiguities can be overcome (Fechler et al, 2012). This indicates that the animals make use of a spatiotemporal sequence of electric images, i.e., electric flow.…”
Section: Discussionmentioning
confidence: 99%
“…Although electric images can be ambiguous (Engelmann et al, 2008), conditioning experiments in Gnathonemus have shown that these ambiguities can be overcome (Fechler et al, 2012). This indicates that the animals make use of a spatiotemporal sequence of electric images, i.e., electric flow.…”
Section: Discussionmentioning
confidence: 99%
“…(C,D)The superposition effect as modeled for a small pair of objects (3×3×3mm). Depending on the gap size, the static electric images (EIs) sum in a non-linear manner and will possibly be non-discriminable (modified from Engelmann et al, 2008). (E)Measured EIs (positive modulation values are normalized to the maximum modulation) for a 20×20×20mm object with a 20mm gap (see blue trace in B).…”
Section: Sensorimotor Patterns In Electrolocation Behaviormentioning
confidence: 99%
“…During this behavior, fish stay stationary next to an object while the tail and trunk are bent towards the object. As a consequence, the EI is subject to large (predictive) distortions influencing both intensity and contrast (Bacher, 1983;Caputi, 2004;Chen et al, 2005;Engelmann et al, 2008;Heiligenberg, 1975;von der Emde et al, 2008). The analysis of these distortions over time could be used to determine the lateral distance to an object (Sim and Kim, 2011).…”
Section: Sensorimotor Patterns In Electrolocation Behaviormentioning
confidence: 99%
“…Weakly electric fish can also experience changes in transdermal potential during tail bending and other body movements, and it has been reported that tail-bending movements of electric fish are strongly related to prey capture (Heiligenberg, 1975;Lannoo and Lannoo, 1993;MacIver, 2001). Tail-bending movements cause large distortions of the electric image (Bastian, 1995;Bastian, 1999, Caputi, 2004Engelmann et al, 2008). However, no study has investigated whether the tail-bending action of weakly electric fish can serve as a localization procedure for a target object near the fish body.…”
Section: Introductionmentioning
confidence: 98%
“…The electrolocation rule of the slope-to-amplitude rate can be applied to the two-dimensional electric image. In threedimensional space, weakly electric fish can initially identify the location of a target object in the rostrocaudal-dorsoventral plane (Engelmann et al, 2008), and the sensory image has peak amplitude at the sensor closest to the object. The lateral distance as another dimension in three-dimensional space is not simply determined but it may be estimated with the relative slope measure described above, that is, the slope-to-amplitude rate of the electric image (von der Emde et al, 1998;von der Emde, 1999;Schwarz and von der Emde, 2001).…”
Section: Introductionmentioning
confidence: 99%